Intrauterine condom catheter tamponade in the management of atonic postpartum haemorrhage: a case series from a tertiary care centre in Central India - Parpillewar, Moushmi B.; Fusey, Shalini S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Postpartum haemorrhage (PPH) is the leading cause of maternal mortality worldwide with a prevalence rate of approximately 6% and 50% is due to atonic PPH. According to WHO 2014- in India 45,000 maternal deaths take place annually and 20-60% are due to postpartum hemorrhage. Various medical and surgical methods are available. Uterine balloon tamponade is one of the methods reported increasingly with good success rates avoiding surgical morbidity. Methods: Prospective data of all women who went into atonic primary PPH after 28 weeks of gestation was collected over a period of one year. Results: Out of the 252 women who had atonic PPH, 23 were inserted with condom balloon catheter after medical management. Success rate was 18/23 (78.2%). Conclusions: Condom catheter is a non-invasive, effective, conservative method of PPH management. In cases of failure it provides a temporary tamponade effect and time to prepare for other interventions.